PERUBAHAN FUNGSI SENI TRADISI RONTEK PACITAN - Tunggul Setyomuryantono; Yosafat Hermawan Trinugraha; Abdul Rahman (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2022)
This study aims to analyze the change in the function of the Rontek traditional art in Pacitan Regency, East Java. The changing process is accompanied by the change in the function of rontek art, from being a daily tradition of the people to wake people up during Sahoor in the month of Ramadan formerly into an annual festival. This study also discusses how the process has become a commodification of culture and at the same time describes the influence of cultural commodification process on the preservation of regional arts in the “Festival Rontek Pacitan (Pacitan Rontek Festival)”. This research approach used qualitative research methods. It was conducted in the administrative area of ​​Pacitan Regency, East Java. Data was collected through in-depth interviews, observation, and documentation. The data analysis technique started with selecting the data and writing it down on a field note, then presenting the data in words in paragraphs and matrices, tables or schematics for easy understanding, and lastly drawing conclusions. Based on the results of the research, the Rontek art that appears in the form of “Festival Rontek Pacitan” presupposes the efforts to preserve the regional arts. The commodification of culture as an effort to preserve the Rontek Pacitan regional art is carried out without reducing the value contained within it.